Sosialisasi Pengolahan Produk Berbasis Potensi Desa: Bakpia Ubi Ungu Di Desa Kotakan Karanganyar Demak - Amnan Haris; Yuda Hanafi Lubis; Zuyun Khoiriyah (Jurnal Bina Desa, 2026)
Indonesia with its abundant natural resources, has long been known as a haven for various types of food crops. One local commodity that deserves attention is sweet potato. Unfortunately, the utilization of sweet potatoes as a staple food or as raw material for the food industry is still not optimal. A socialization and training program on product processing based on village potential was held on July 31, 2024, in Kotakan Village, Karanganyar, Demak. The program aimed to empower the community, especially the women of the Family Welfare Movement (PKK), by optimizing the local potential of purple sweet potatoes into economically valuable products, namely purple sweet potato bakpia. A total of 20 participants, consisting of PKK women, took part in the training. In this event, participants gained knowledge and skills regarding the production process of purple sweet potato bakpia, from raw material preparation to product packaging techniques. Through this training, it is hoped that the community can develop micro-businesses based on local potential, increase family income, and strengthen the village's economic independence. The results of the activity showed high enthusiasm from the participants and the potential for developing purple sweet potato bakpia as a unique culinary icon of the village.